1980
DOI: 10.1093/bja/52.11.1117
|View full text |Cite
|
Sign up to set email alerts
|

Spinal and General Anaesthesia in Total Hip Replacement: Frequency of Deep Vein Thrombosis

Abstract: Subarachnoid block (SAB) or general anaesthesia (GA) was induced in 85 patients undergoing total hip replacement. The frequency of deep vein thrombosis (DVT), assessed by fibrinogen uptake studies and venography, was 29% in those patients receiving SAB and 54% in the GA group. Total blood loss (intra-operative and post-operative wound suction drainage) in SAB group was 66% and total transfusion volume 52% of that of GA group. No morbidity attributable to SAB or to the associated arterial hypotension was detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1
1

Year Published

1983
1983
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(37 citation statements)
references
References 5 publications
(5 reference statements)
2
32
1
1
Order By: Relevance
“…This relationship has been repeatedly described in the hip arthroplasty literature 4,5,7,[21][22][23][24][25][26][27][28][29] . Blood loss during total hip arthroplasty performed under general anesthesia is often a function of how well a low blood pressure is maintained during the procedure 28 .…”
Section: Discussionmentioning
confidence: 86%
“…This relationship has been repeatedly described in the hip arthroplasty literature 4,5,7,[21][22][23][24][25][26][27][28][29] . Blood loss during total hip arthroplasty performed under general anesthesia is often a function of how well a low blood pressure is maintained during the procedure 28 .…”
Section: Discussionmentioning
confidence: 86%
“…Furthermore, hip replacement is followed by a high incidence of postoperative deep venous thrombosis unless prophylactic measures are taken (Modig et al 1981, Thorburn et al 1980). …”
Section: Introductionmentioning
confidence: 99%
“…They concluded that SA can consider as an effective alternative to GA for lumbar spine surgery as it had lower incidence of minor complications. (7) As previous studies showed, SA reduced blood loss for lower limb orthopedic and vascular surgeries compared to GA. (8)(9)(10)(11) The decreased blood loss during spinal anesthesia likely contributed to the lower surgical time, and less bleeding would facilitate dissection and result in less time needed to effect hemostasis prior to surgical closure. Reduced rate of bleeding within the wound has been suggested as one factor that may contribute to a shorter surgical time in spinal anesthesia In addition, although surgeons are interested in spinal anesthesia as a more reliable method, experience shows the prolonged operation performed in the prone position under spinal anesthesia increases the surgeon's stress and anxiety.…”
Section: Discussionmentioning
confidence: 99%